Fabrication of nanomaterials and related devices - Tay, Beng Kang (2012)
Nanotechnology refers broadly to a field of applied science and technology with a unified theme of control of mater on the nano-meter scale, and fabrication of devices at this scale. In this project, amorphous silica nanowires have been successfully fabricated from the mixture of ZnCh, and V02 on silicon substrate by controlling the conditions of the vapor-phase transport. Ultra-long cotton-like nanowires with diameters of 20 to 50 nm show strong photoluminescence of red and green light originated from surface NBOHC defect and nonstoichiometric structure. The morphology of SiOx is dependent on synthesis